Microstructure and mechanical properties of pure titanium prepared by powder metallurgy combined with hot extrusion and rotary swagin - LIU Xiao-min; GAO Hong-liang; YANG Jing-ran; FU Zheng-rong; LI Xing-fu; LI Cong; YANG Yi; LIU Huan; ZHU Xin-kun (Fenmo yejin jishu)
Pure titanium rods were prepared by the powder metallurgy technology combined with the hot extrusion and the rotary swaging. The yield strength, Vickers hardness, microstructure, and relative density of the pure titanium rods were tested by the universal testing machine, Vickers microhardness tester, metallographic microscope, and high-precision multifunctional densitometer. The effects of preparation technology and microstructure on the mechanical properties of the pure titanium rods were studied. The results show that, the yield strength of pure titanium rods prepared by the powder metallurgy combined with the hot extrusion and rotary forging is 880 MPa, the uniform elongation is 4.06%, and the ductile fracture occurs during the tensile deformation. The microstructure of pure titanium rods is equiaxed fine grain structure, the average grain size is about 1 μm, the structure distribution is uniform, showing no obvious cracks and defects and high relative density.